Behavior of palm oil fuel ash and metakaolin ternary blend cement mortar at elevated temperatures - Usman, Jamilu (American Society of Civil Engineers, 2017)
This study examines the effect of a ternary blend of palm oil fuel ash (POFA) and metakaolin (MK) on the behavior of cement mortar exposed to elevated temperatures. The ternary blend was produced by combining 10% POFA and 10% MK by weight as a substitute to cement. Three additional samples which include plain portland cement (OPC), 20% MK binary and 20% POFA binary were also produced for comparison. Compressive strengths and ultrasonic pulse velocities of the mortar samples after heating to temperatures of 200, 400, 600, and 800°C for 2 h were assessed. Furthermore, X-ray diffraction, Fourier transform infrared spectroscopy, and field emission scanning electron microscopy analysis were carried out to examine the microstructure of the samples. The results show that the compressive strength and microstructure of mortar exposed to elevated temperatures improved with the simultaneous use of POFA and MK compared to plain OPC mortar and when POFA or MK is singly used. The ternary blend of cement/POFA/MK can, therefore, be used as a fire resistant material.